Política de expansão da educação superior no Brasil - o prouni e o fies como financiadores do setor privado - AMARAL, Nelson Cardoso (Universidade Federal do Pará, 2019)
The study analyzes the expansion policy for Brazilian higher education in the period 2003 through 2014, emphasizing the analysis of ProUni and FIES as private sector financers. The methodological resources encompassed both quantitative and qualitative research procedures, consulting documental sources and the websites of the Department of Federal Revenue of Brazil and the Federal Senate to gather general financial data, and the website of the Higher Education Census to gather financial data about enrollments and higher education institutions. The study has evidenced that an expansion policy occurred for both private and public sectors, and that the private sector received substantial support from the Government, especially through the ProUni and FIES programs, which has contributed to the achievement of profit, while providing a higher education model that dissociates undergraduate education from research and extension activities.